A Mixture of Herbal Gel Formulation and Evaluation of Jatropha curcas and Euphorbia tirucalli for Wound Healing - Oktavia, Maria Maulina; Suwitono, Marvel Reuben (Jurnal Biologi Tropis, 2025)
Wounds are tissue disorders that require appropriate treatment to accelerate healing. Natural ingredients such as Jatropha curcas and Euphorbia tirucalli leaves have the potential as alternative wound healing agents. This study aims to formulate and evaluate a gel preparation combining extracts of both plants for wound care. Extraction was carried out using 96% ethanol by maceration, followed by formulation with HPMC as a gelling agent at various extract concentrations. The gel was evaluated based on organoleptic properties, homogeneity, pH, viscosity, spreadability, and adhesiveness. The results showed that the gel exhibited good physical stability, a uniform texture, a comfortable pH on the skin (4.5–6.5), and a viscosity suitable for topical application. Phytochemical compounds such as flavonoids, saponins, and tannins contribute to its antibacterial and anti-inflammatory activities, thereby accelerating wound healing. Therefore, the combined extract of Jatropha curcas and Euphorbia tirucalli has promising potential as a herbal gel formulation for wound healing. In conclusion, the combination of Jatropha curcas leaf extract and bone-breaking leaf extract has the potential to be developed as a natural active ingredient in a safe and environmentally friendly wound healing gel formulation.